Real-world data on nivolumab treatment of non-small cell lung cancer. (4th March 2017) - Brustugun, O.T.; Sprauten, M.; Helland, Å.
Abstract: Background: Checkpoint inhibitors have proven effectiveness in clinical trials for non-small cell lung cancer (NSCLC) patients, but if this is congruent with routine patient care is discussed. We present real-world experience with the PD1-inhibitor nivolumab in NSCLC. Patients and methods: Patients with NSCLC were considered eligible for nivolumab treatment after one or more lines of chemotherapy, and when in reasonable performance status (PS) [Eastern Cooperative Oncology Group (ECOG) < 3]. Treatment was given according to guidelines in the two phase III studies, CA209017 and CA209057. Response evaluation was done according to Recist 1.1, and treatment given until unequivocal progression or intolerable toxicity. Results: Fifty-eight patients (30 females) commenced therapy in the period June–August 2015. Median age was 64.6 years (range 32.3–88.2). Twenty-four patients had squamous cell carcinoma and 32 adenocarcinoma, 38 had received two or more prior lines of therapy. Fourteen cases (24%) were in ECOG PS 2. After a medium observation time of 14.3 months, 13 (22%) are still in treatment. Median time to treatment failure (TTF) was 4.0 months, 34% were off treatment during the first two months. Median overall survival (OS) is 11.7 months. There was no difference in TTF or OS among patients with squamous versus non-squamous histology or between 1 versus >1 prior line of therapy. Four patients (7%) were off treatment due to toxicity, none were grade 4 or 5. Conclusion: Nivolumab treatment outside clinical trials seems to perform as expected.